GREYWATER IN INDONESIA: CHARACTERISTIC AND TREATMENT SYSTEMS - Mayrina Firdayati; Asri Indiyani; Maria Prihandrijanti; Ralf Otterpohl (Jurnal Teknik Lingkungan, 2015)
Abstract: Lacking in centralized wastewater treatment plant exist in all Indonesian cities. Drainage and river suffer from domestic wastewater contaminants. It also increases cost of water treatment plant operation if river used as water source. Using of greywater treatment system is believed as new solution. This paper will review application of greywater treatment in Indonesia. Some projects exist but most of them need supports from third party and their initial costs are high. Thus, low cost and reuse system in small community or household are important. Researches showed that constructed wetland is quite promising because the reduction of BOD concentration can reach 60-94%. However, land requirement and greywater generation could be the limitation and Anaerobic Baffled Reactor can be used as an alternative. Key words: domestic wastewater, greywater, reuse, decentralized wastewater treatment system, low cost treatment system, constructed wetlands